Distribution feeder loss calculation using artificial neural network - Garrido, Rolando C. (2006)
Under today's operating environment, a more efficient management and operation of power system is required from electric utilities. With the allowable loss that could be passed on to the consumers being limited, utilities are motivated to improve their efficiency in order to avoid paying the penalty. To be able to achieve this, loss analysis, especially at the distribution level where about 70% to 80% of the total system loss occurs, will have to be done more often now than ever. This thesis presents a fast yet accurate loss evaluation methodology using an Artificial Neutral Network (ANN) model to calculate the hourly losses in Meralco's distribution feeders. Energy losses were consequently calculated by integrating the hourly losses over the given period of time. The PathFinder Neutral Network System was used in developing the neutral network model. The network architecture adopted was based on a three-layer feedforward network. The ANN networks derived proved to be accurate in predicting the hourly losses and the energy losses over a given period of time. Mean Absolute Percent Error of less than 3% were consistently achieved, with some cases achieving less than 1%. Maximum percent error on each individual prediction also did not exceed the 5% set limit.